Unidentified man in laboratory (1920)
General view of an unidentified man, presumably a laboratory assistant, posed near a work bench with assorted scientific apparatus and glassware visible in the background. While the setting of this photograph is also unidentified, the photo was donated along with other materials related to the Hospital of the Rockefeller Institute for Medical Research (H.R.I.M.R.) and may depict a laboratory at that facility. However, there is no contextual information directly linking this photo to the H.R.I.M.R.
Keywords: Employees; Scientific apparatus and instruments; Glassware; Laboratories